2015
DOI: 10.1161/jaha.115.002553
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Heart–Liver Axis: Matrix Metalloproteinase‐2 Negatively Regulates Cardiac Secreted Phospholipase A 2 to Modulate Lipid Metabolism and Inflammation in the Liver

Abstract: BackgroundEndocrine functions of the heart have been well established. We investigated the hypothesis that cardiac secretion of a unique phospholipase A2 recently identified by our laboratory (cardiac secreted phospholipase A2 [sPLA 2]) establishes a heart–liver endocrine axis that is negatively regulated by matrix metalloproteinase‐2 (MMP‐2).Methods and ResultsIn Mmp2 −/− mice, cardiac (but not hepatic) sPLA 2 was elevated, leading to hepatic inflammation, immune cell infiltration, dysregulation of the sterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 60 publications
4
46
0
Order By: Relevance
“…We recently found that in Mmp2 −/− mice, the heart secretes an as yet unidentified PLA 2 (cardiac sPLA 2 ), which circulates in plasma, acting as a signal that is governed by MMP‐2 and that modulates lipid metabolism in the liver . In Mmp9 −/− mice, plasma sPLA 2 activity was significantly higher than in WT plasma but otherwise was normal in the heart, as demonstrated by assaying the generation of free thiol from di‐heptanoyl‐thio‐phosphatidylcholine (substrate) (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently found that in Mmp2 −/− mice, the heart secretes an as yet unidentified PLA 2 (cardiac sPLA 2 ), which circulates in plasma, acting as a signal that is governed by MMP‐2 and that modulates lipid metabolism in the liver . In Mmp9 −/− mice, plasma sPLA 2 activity was significantly higher than in WT plasma but otherwise was normal in the heart, as demonstrated by assaying the generation of free thiol from di‐heptanoyl‐thio‐phosphatidylcholine (substrate) (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Data are representative of technical duplicates. For comparison, the activity of cardiac sPLA 2 from an Mmp2 −/− mouse (mouse “E” in figure S3 of Hernandez‐Anzaldo et al) is presented. * P <0.05 vs Mmp2 −/− plasma, t test.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations